Structure-dependent iron-based metal–organic frameworks for selective CO2-to-CH4 photocatalytic reduction. Issue 48 (27th November 2020) - Dao, Xiao-Yao; Guo, Jin-Han; Zhang, Xiao-Yu; Wang, Shi-Qing; Cheng, Xiao-Mei; Sun, Wei-Yin
Abstract : MIL-100(Fe) exhibits superior activity and selectivity for CH4 generation under visible-light irradiation compared with MIL-101(Fe). Abstract : Visible-light driven reduction of carbon dioxide (CO2 ) to methane (CH4 ) is a challenge in the photocatalytic reaction system. Herein, two Fe-based metal–organic frameworks (MOFs) MIL-100(Fe) and MIL-101(Fe) with single-trimetallic clusters but distinct organic ligands were employed to explore the structure-dependent CO2 conversion performance. Compared with MIL-101(Fe), MIL-100(Fe) exhibits superior catalytic activity and selectivity for CH4 generation under visible-light irradiation via a solvent-free route. This is the first report that MIL-100(Fe) finishes the photoreduction of CO2 into CH4 . Importantly, the plausible conversion pathways of the reaction were given by density functional theory (DFT) calculations. This work furnishes new direction for constructing MOFs to achieve CO2 -to-CH4 conversion.